NEW URBAN ECONOMIC AGENTS: A COMPARATIVE ANALYSIS OF HIGH-PERFORMANCE NEW ENTREPRENEURS - Kourtit, Karima; Nijkamp, Peter; Suzuki, Soushi (Quaestiones Geographicae, 2016)
Migrants are often the carriers of new skills and original abilities. This study focuses on the importance of ‘new urban entrepreneurship’ – in particular, ethnic or migrant business firms – as a major driver of creative and urban dynamics and economic vitality in urban agglomerations. The paper offers a general account of both backgrounds and socio-economic implications of migrant entrepreneurship in large agglomerations and highlights the socio-economic heterogeneity in motivation and performance among different groups of migrant entrepreneurs. This demographic-cultural diversity prompts intriguing questions about differences in business performance among distinct groups of migrant entrepreneurs, even in the same ethnic group. In the paper, a recently developed and amended version of data envelopment analysis (DEA), viz. super-efficiency, is presented and applied to a group of Moroccan entrepreneurs in four large cities in the Netherlands. The main research aim is (i) to identify the best-performing firms (so-called ‘entrepreneurial heroes’) from a broad management and business perspective, while (ii) the background of our findings are more thoroughly analysed. The paper ends with some general concluding remarks on urban business strategies.